Erufosine (ErPC3) Cationic Prodrugs as Dual Gene Delivery Reagents for Combined Antitumor Therapy. Issue 68 (4th November 2019) - Gaillard, Boris; Seguin, Cendrine; Remy, Jean‐Serge; Pons, Françoise; Lebeau, Luc
Abstract: Sixteen cationic prodrugs of the antitumor alkylphospholipid (APL) erufosine were rationally synthesized to provide original gene delivery reagents with improved cytotoxicity profile. The DNA complexation properties of these cationic lipids were determined and associated transfection rates were measured. Furthermore, the self‐assembly properties of the pro‐erufosine compounds were investigated and their critical aggregation concentration was determined. Their hydrolytic stability under pH conditions mimicking the extracellular environment and the late endosome milieu was measured. Hemolytic activity and cytotoxicity of the compounds were investigated. The results obtained in various cell lines demonstrate that the prodrugs of erufosine display antineoplastic activity similar to that of the parent antitumor drug but are not associated with hemolytic toxicity, which is a dose‐limiting side effect of APLs and a major obstacle to their use in anticancer therapeutic regimen. Furthermore, by using lipoplexes prepared from a prodrug of erufosine and a plasmid DNA encoding a pro‐apoptotic protein (TRAIL), evidence was provided for selective cytotoxicity towards tumor cells while nontumor cells were resistant. This study demonstrates that the combination approach involving well tolerated erufosine cationic prodrugs and cancer gene therapy holds significant promise in tumor therapy. Abstract : Dual erufosine prodrugs : Biolabile cationic derivatives of the antiproliferative alkylphospholipid erufosine have been synthesized and show combined antitumor activity with a plasmid encoding the tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL), with selectivity for tumor vs. nontumor cells.